2008
DOI: 10.1097/pec.0b013e3181850ca3
|View full text |Cite
|
Sign up to set email alerts
|

Oxycodone Versus Codeine for Triage Pain in Children With Suspected Forearm Fracture

Abstract: Triage-administered O tended toward greater pain reduction compared with C in children with suspected forearm fractures. Although minor adverse effects occurred in both groups, itching occurred more in C. Identification of radiography as the most painful part of fracture evaluation underscores the need for early triage administration of analgesia for suspected fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Oral oxycodone was more effective and produced less itching than codeine, but early administration at triage was required as having Xrays, rather than examination or casting, was identified as the most painful period (Charney et al, 2008 Level II).…”
Section: Chapter 10mentioning
confidence: 99%
“…Oral oxycodone was more effective and produced less itching than codeine, but early administration at triage was required as having Xrays, rather than examination or casting, was identified as the most painful period (Charney et al, 2008 Level II).…”
Section: Chapter 10mentioning
confidence: 99%
“…2 The popularity of hydrocodone/acetaminophen postdischarge is supported by two small clinical trials, 3,4 and several other studies that compare the efficacy of commonly prescribed oral opioids in different settings. [5][6][7][8][9] There has been increasing concern about the abuse of oral opioids in patients discharged from the ED. 10,11 The efficacy of hydrocodone versus codeine has not been adequately studied among discharged adult ED patients with acute pain.…”
mentioning
confidence: 99%
“…4 The group found that 50% of children in the ibuprofen group achieved adequate analgesia, and this was more than codeine (40%) or acetaminophen (36%). 4 In another study, Charney et al 5 randomized 177 children with suspected orthopedic injury to receive either codeine (2 mg/kg) or oxycodone (0.2 mg/kg). Although both groups had significant reductions in pain scores measured every 30 minutes for 3 hours, children who received oxycodone had statistically significant greater reduction in pain scores compared with codeine at all time intervals.…”
Section: Codeinementioning
confidence: 99%
“…Although both groups had significant reductions in pain scores measured every 30 minutes for 3 hours, children who received oxycodone had statistically significant greater reduction in pain scores compared with codeine at all time intervals. 5 Codeine metabolism and genetic polymorphism of CYP2D6 Since codeine has a very low affinity for opioid receptors, its analgesic effect is dependent on its conversion to morphine through the cytochrome P-450 enzyme 2D6 (CYP2D6). 6 CYP2D6 catalyzes the conversion of codeine into morphine.…”
Section: Codeinementioning
confidence: 99%